2023
DOI: 10.1146/annurev-med-043021-033013
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-Associated Virus Gene Therapy for Hemophilia

Abstract: In vivo gene therapy is rapidly emerging as a new therapeutic paradigm for monogenic disorders. For almost three decades, hemophilia A (HA) and hemophilia B (HB) have served as model disorders for the development of gene therapy. This effort is soon to bear fruit with completed pivotal adeno-associated viral (AAV) vector gene addition trials reporting encouraging results and regulatory approval widely anticipated in the near future for the current generation of HA and HB AAV vectors. Here we review the clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 89 publications
2
39
0
Order By: Relevance
“…Importantly, however, the same animals were followed-up for 10 years without evidence of tumorigenesis; nonetheless, this study provides the first large-animal data to highlight the risk of AAV-mediated integration. 58 …”
Section: Requirements For Implementing Gene Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, however, the same animals were followed-up for 10 years without evidence of tumorigenesis; nonetheless, this study provides the first large-animal data to highlight the risk of AAV-mediated integration. 58 …”
Section: Requirements For Implementing Gene Therapymentioning
confidence: 99%
“…In the short-term, haemophilia treatment centres will require additional resources to coordinate care and follow-up of gene therapy recipients. 58 Both physicians and nurses will become heavily involved in patient education; additional investment in psychosocial support may be required, as will be new processes for ordering, storing, and handling gene therapy products, with possible repercussion on the pharmacists. During the first months following gene therapy, the liver health must be closely monitored, with additional workload on hepatologists.…”
Section: Haemophilia Care Centresmentioning
confidence: 99%
“…This raises concerns about the durability and safety of AAV-based liver-specific gene therapy. Currently, several AAV-based gene transfer strategies have been modified and clinical trials have been initiated, which could offer hope to improve the durability and safety of this therapy for patients with hemophilia ( 140 143 ).…”
Section: Novel Strategies For Eradicating Inhibitors or Immune Tolera...mentioning
confidence: 99%
“…[22][23][24][25][26][27][28] Gene therapy clinical trials for adults with haemophilia were initiated three decades ago and have demonstrated cautiously optimistic results. 29 Still, no human clinical trials have been approved for prenatal cell and/or gene therapy for haemophilia, despite its potential for providing a curative solution for this population.…”
Section: Introductionmentioning
confidence: 99%